Five novel EP300 variants expand the genetic and phenotypic spectrum of Rubinstein–Taybi syndrome type 2 in Chinese patients - Zhang, Qiang; Yang, Qi; Zhou, Xunzhao; Qin, Zailong; Luo, Jingsi (Frontiers in Genetics, 2025)
IntroductionRubinstein-Taybi syndrome type 2 (RSTS2; OMIM #613684) is a rare autosomal dominant disorder caused by loss-of-function variants in the EP300 gene (OMIM #602700), characterized by intellectual disability, distinctive craniofacial features, and skeletal anomalies.MethodsWhole-exome sequencing (WES) was performed on five pediatric patients presenting with neurodevelopmental delay. Candidate variants were filtered using the TGex platform and validated by Sanger sequencing for familial segregation analysis. The functional impact of variants was assessed using diverse bioinformatic tools, and pathogenicity classifications were assigned according to ACMG/AMP guidelines.ResultsFive novel EP300 variants were identified in this study: c.4774A>G (p.Lys1592Glu), c.4452 + 5G>C, c.3764A>G (p.His1255Arg), c.3591–2A>G, and c.6439C>T (p.Gln2147*). These alterations impair gene function through mechanisms including amino acid substitution, disruption of mRNA splicing, or premature protein truncation. All variants were classified as pathogenic or likely pathogenic per ACMG/AMP criteria. Literature analysis reveals that the predominant clinical manifestations in the Chinese patients encompassed neurodevelopmental impairment, accompanied by motor delay, growth retardation, and microcephaly. Strikingly, archetypal craniofacial dysmorphisms, such as arched eyebrows, long eyelashes, downslanting palpebral fissures, beaked nose, as well as significant skeletal abnormalities were absent, suggesting EP300 variants may present with a broader and more variable phenotypic spectrum than previously recognized.ConclusionThis study reports five novel pathogenic EP300 variants, expanding the variant repertoire of RSTS2 and providing an important basis for clinical diagnosis and genetic counseling.